Alkalization of dissolving cellulose pulp with highly concentrated caustic at low NaOH stoichiometric excess. (1st June 2017) - Albán Reyes, Diana Carolina; Gorzsás, András; Stridh, Kjell; de Wit, Paul; Sundman, Ola
Highlights: The manuscript investigates LWC (low water content) mercerisation. The co-influence by experimental parameters was previously not known. A diffusion controlled mercerisation mechanism is presented. Abstract: We present a quantitative study, using Raman spectroscopy combined with multivariate data analysis, to determine the degree of activation of softwood sulphite dissolving cellulose pulp by aqueous sodium hydroxide. We have chosen industrially relevant conditions, including low stoichiometric ratio of NaOH/Anhydroglucose Unit (AGU) < 2 and highly concentrated caustic (≥45% w/w [NaOH]). A design of experiments is used to investigate the effects of simultaneous variation of a set of key parameters on the degree of activation ( i.e. transformation to alkali cellulose, denoted as DoA): (a) the NaOH/AGU stoichiometric ratio, denoted (r); (b) the concentration of NaOH, denoted [NaOH]; (c) temperature, denoted (T); and (d) reaction time, denoted (t). Solid-state 13 C CP/MAS NMR spectroscopy was applied to investigate the reproducibility of the experiments and to select the range for (t). According to the model, (r) is found to have a statistically significant effect on DoA (increasing from DoA = 6–30% at the lowest (r) = 0.8, to DoA = 48–87% at the highest (r) = 1.8), together with [NaOH]. The influence of [NaOH] depends strongly on (r). The other studied variables are found to be insignificant in the model and has a complicated influence on the activation. In particular, (T) is found to be unimportant in the studied range (30–60 °C), but increasing (t) from 5 to 25 min shows a positive influence on DoA, depending on both (r) and [NaOH]. A mercerisation mechanism that is controlled by diffusion is proposed to explain these phenomena.